Monitoring Long-Term Wheat Cultivation and Climatic Drivers for Land Use Change: A Case Study Using Remote Sensing at Thakurgaon Sadar in Bangladesh (Journal of Environmental Science and Natural Resources, 2022)
The present study uses Remote Sensing techniques to monitor long-term wheat cultivation in Thakurgaon Sadar Upazila. Multi-spectral Landsat images from 1999 to 2019 at five years intervals were collected at the maximum growth stage of wheat. The images were processed by QGIS, ArcGIS, and R software with the random forest supervised classification. The findings revealed that images were classified and separated the crops successfully due to cloud-free images and pure pixels. The results show that the wheat area was decreased from 1999 (16349 ha) to 2019 (9161 ha). It was due to the transformation of the wheat area into other crop areas. The shrinkage rate of wheat areas was much higher (10.93 %) in 1999-09 than in 2009-19. It was due to a sudden decline in blast disease during 2005-09 and increased again. The shrinkage of the wheat area has been driven mainly by climate change influencing profitability. Prolonged hydrological drought introduced maize and potato in the wheat area. The benefit-cost ratio decreased gradually in wheat but increased in maize and potato. The study demonstrates that remote sensing is an effective method for wheat crop area monitoring. This study will help us understand the status of long-term wheat cultivation.Environ. Sci. & Natural Resources, 13(1&2): 25-37, 2020